Restoring the memory of the Jewish minority in a cityscape: a case study of Poznań - Duda-Seifert, Magdalena (Rozwój Regionalny i Polityka Regionalna, 2025)
The landscapes bear different memories which can be held, sustained, forgotten, or erased by local communities. As the local society is usually non-homogeneous, there are different memories, and the policy of memory depends on the politics and also on global social trends. Especially difficult is the situation of minorities, whose memory is dominated in the cityscape by the ruling majority. The author focuses on the analysis of Jewish memory carriers using the case study of Poznań in Poland. As a result, forty of them have been defined and analysed in a cityscape. There are many actors involved, and the process of restoring memory to the landscape has accelerated in the last 25 years, but it is still at its beginnings.